THE “TEACHER” PHENOMENON IN THE HISTORICAL AND PHILOSOPHICAL SPACE OF CULTURE - Khushbokov, Oybek (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article explores aspects of the sociocultural phenomenon of a teacher regarding spiritual life. The problem of studying the phenomenon of “Teaching” is a very important aspect within the framework of the development of society. In each culture the teacher has his own characteristics related to historical, cultural and social factors.